Decolorization and degradation of azo dyes in thermophilic biological wastewater treatment process: A mini-review - Kiem-Hao Phan; Linh-Thy Le; Thanh-Tung N. Ninh; Cong-Sac Tran; Thanh-Tin Nguyen; Dang-Tien-Dat Nguyen; Van-Tung Tra; Thanh-Dai Tran; Thanh-Binh Nguyen; Thanh-Phong Mai; Chettiyappan Visvanathan; Xuan-Thanh Bui (Case Studies in Chemical and Environmental Engineering)
Azo dyes comprise xenobiotic compounds characterized by the azo group (-NN-). The textile industry primarily consumes this type of dye, discharging significant amounts of textile wastewater with high pollution levels and temperature, necessitating treatment solutions to reduce costs and minimize environmental and human health risks. Thermophilic processes are believed to have rapid substance degradation rates, low sludge production, and cost-saving benefits for water cooling. However, research on treating azo textile-dying wastewater with a thermophilic decolorization process remains relatively limited. From the mentioned information, this study examines the thermophilic process, which exhibits superior color removal compared to the mesophilic process. Besides, the role of enzymes in the thermophilic decolorization process is elucidated. The research investigates the anaerobic thermophilic decolorization process as well as the aerobic degradation of azo dyes under thermophilic temperature conditions. A coupling method for decolorization treatment toward complete mineralization is explored, and the azo dye decolorization through enzyme activities is analyzed. The findings provide insights into the efficient and environmentally friendly removal of azo dyes using thermophilic processes and the involvement of enzymatic activities in the decolorization process.